Physics-Based Scientific Learning Module to Improve Students Motivation and Results - Soni Nugroho Yuliono; Sarwanto Sarwanto; Cari Cari (Journal of Education and Learning (EduLearn), 2018)
Teaching materials that available in the school to learn physics especially scientific-based is limited and become one of the obstacles to achieving the learning objectives on electromagnetic waves material. The research aims are to gain scientific Physics-based learning modules for high school grade XII students who have met the eligibility criteria, determine the effectiveness of using scientific-based learning modules Physics to improve motivation and learning outcomes from students of grade XII High School. The development of this research on Physics module using 4D development procedure which consists of the steps of define, design, development, and dissemination. Definition phase consists of the teacher and student’s needs analysis process, material analysis, as well as the formulation of the learning module. The design phase of physics learning modules according to the stage of scientific learning is integrated into the module. The development phase consists of the development process of the modules from the design results, validating the feasibility, module revision, limited testing, and the use of scientifically-based learning modules Physics in grade XII IPA 1 Batik 2 Surakarta senior high school. The deployment phase is the deployment process module to another Senior High School in Surakarta. Data Analysis for the study is a quantitative descriptive analysis based on the score criteria and analysis of increasing student motivation through N-gain. Conclusion obtained are; 1) Physics-based scientific learning modules that developed meet the eligibility criteria on aspects of content and presentation, language, the chart, and aspects of learning. The module is declared worthy of the ideals validation results with the percentage of 85.16%, 83.66% by students and teachers in the response phase of the deployment of 85.93%, which is included in the category of "very good"; 2) Physics-based scientific learning modules with material scientific electromagnetic waves can increase students' motivation to gain value 0.4 or in the category "medium".